ANALISIS DAMPAK PANDEMI COVID19 TERHADAP PERGERAKAN ORANG KE KAWASAN KOMERSIAL BERDASARKAN PENGGUNAAN LAHAN PARKIR (Studi Kasus Suzuya Mall Banda Aceh) - Juliana Fisaini; Muhammad Isya (FROPIL (Forum Profesional Teknik Sipil), 2021)
The Covid19 pandemic has affected various aspects of human life, including trips for daily activities. This phenomenon occurred very significantly at the beginning of the pandemic period due to social restrictions by the government. This study aims to analyze the movement of people to commercial areas at the beginning of the pandemic in Banda Aceh, by recording parking data. This study investigate the commercial area of ​​the Suzuya Mall Banda Aceh City shopping center. The data collected consisted of data on the use of parking lots before and during the start of the pandemic, during which the social distancing appeal was imposed in the City of Banda Aceh. The data collection method is done by taking secondary data, namely parking land use data that comes from an automatic parking recording machine. Data analysis was carried out descriptively based on data on vehicles entering the parking lot in the review area. This data is processed in the form of fluctuations in the number of vehicles per day during the data collection period. This analysis can also identify the effectiveness of government calls for social distancing. The results show that there is a 70,4% (motorcycle) and 57,53% (car) decrease in the movement of people to commercial areas.However, it is evident that the amount of the allowance increased at the end of the first week of social restriction. It can be concluded that the appeal for social restrictions from the government affects people's behavior in carrying out movements during a pandemic.